Delicts against the Sixth Commandment of the Decalogue in the 1983 Revised Book VI of the Code of Canon Law - Borek, Dariusz (Prawo Kanoniczne, 2022)
The article entitled Delicts against the Sixth Commandment of the Decalogue in the Revised Book VI of the 1983 Code of Canon Law analyses the most recent provisions of the Catholic Church concerning the penal protection of the Sixth Commandment of the Decalogue. The essential source is therefore Book VI of the Code of Canon Law in the amended version of 2021. In addition, it was also necessary to refer to the changes made in the special law motu proprio Sacramentorum sanctitatis tutela and the other statutory interventions of Pope Francis due to the interconnectedness of the issues discussed in the present article. It should be noted that the Code of Canon Law, both before and after the 2021 amendment, does not explicitly provide for the penal protection of the sixth commandment of the Decalogue. Nevertheless, values related to the content of the sixth commandment are criminally protected in various places in Part II of Book VI of the Code of Canon Law. This is particularly evident in the case of can. 1395 and can. 1398, which explicitly refer to contra sextum violations as canonical offences. In the first of the cited canons, offences contra sextum are seen from the perspective of offences against the special duties of the clerical state. In the case of the second canon, on the other hand, we are dealing with contra sextum offences categorized as offences against human life, dignity, and freedom. From an analysis of can. 1395 and can. 1398, it is clear that we are currently dealing with a significant widening of the material and personal scope concerning the protection of values related to the sixth commandment of the Decalogue. After the 2021 amendment, contra sextum violations are considered not only from the perspective of violations against the special duties of the clerical state, but also from the perspective of the protection of human life, dignity, and freedom.